Distributional Implications of Government Tax and Expenditure Policies : Issues, Problems, and Methodology. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper examines the methodological issues arising in the measurement of the distributional impact of tax and expenditure policies, with emphasis on the problems related to the measurement of the impact of adjustment programs on the welfare of the poor. Both conceptual and empirical considerations suggest that public expenditures are a more potent instrument for distributional purposes than taxes but are also more difficult to analyze and evaluate. The paper concludes that more research is needed toward a better measurement of expenditure benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet